RelB regulates the homeostatic proliferation but not the function of Tregs - Zhou, Shuping (BMC Immunol, 2020)
BACKGROUND: RelB, a member of the NF-κB family, plays a critical role in the development of T cells. However, the role of RelB in Foxp3(+) regulatory T cells (Tregs) remains controversial. RESULTS: Using a bone marrow chimeric mouse model, we demonstrated that the expansion of Foxp3(+) Tregs in vivo could be mediated by extrinsic mechanisms. RelB plays an important role in inhibiting the homeostatic proliferation of Tregs, but not their survival. Even with the heightened expansion, RelB(−/−) Treg cells displayed normal suppressive function in vitro. Among the expanded populations of Treg cells, most were nTreg cells; however, the population of iTregs did not increase. Mechanistically, RelB seems to regulate Treg proliferation independently of the signal transducer and activator of transcription 5 (STAT5) pathway. CONCLUSIONS: These data suggest that RelB regulates Treg proliferation independently of the STAT5 pathway, but does not alter the function of Tregs. Further studies are warranted to uncover such mechanisms.